Warrant economics, call-put policy options and the fallacies of economic theory - John Hatgioannides; Marika Karanassou (Queen Mary University of London, School of Economics and Finance, 2011)
In this paper we aim to trace the roots of the ongoing economic mayhem and to unmask the chorus of the tragedy which plays on the world stage. The main thesis of our work is that, despite the triumphant rhetoric praising the merits of perfect competition, the global fields of the dysfunctional market system have mushroomed in what we call Warrant Economics for the Free-Market Aristocracy. Warrant Economics unfolds in two symbiotic tenets that constitute the subtle architecture of the neoliberal edifice: (i) the systemic creation and preservation of inequality via Call-Put policy options, and (ii) the systemic exploitation of inequality via novel and toxic forms of securitisation. In effect, the power structure of insiders' capitalism that we describe, through the costless appropriation of an intricate cobweb of Call-Put structures, has distorted competition and accelerated economic concentration. We view the income distribution effect, which favours the top 1%, and the business concentration effect, which gravitates competition towards oligopolistic/monopolistic industries, as the two sides of the Warrant Economics coin. We argue that the Warrant Economics state of capitalism has been legitimised by a degenerating research programme blossomed under the fallacy that economics is the physics of society. In this faculty of thought, we perceive the Great Recession as a symptom of Warrant Economics, rather than as a tsunami-like event.
Keywords: E66; G01; G10; 330; Warrant Economics; Call-Put policy options; securitisation; monopoly; income distribution; Great Recession; sovereign debt